Evaluating the Internal Quality of the Master's Curriculum in Auditing in Iran: Perspectives of Faculty and Students - Zahra Dianati Deilami; Mohammad Mehdi Noori; Hossein Abbasian (بررسی‌های حسابداری و حسابرسی)
ObjectiveThis research aims to assess the internal quality level of the Master's curriculum in Auditing from the perspectives of professors and students in this field, based on the nine elements of the Francis Klein model. The goal is to inform the curriculum developers about the program's success rate in achieving the desired educational objectives (in what ways it has been effective and in what ways it needs to be changed or supplemented) and to facilitate decision-making for its improvement to achieve the desired efficiency and outcomes.MethodsThis research is quantitative and classified as a descriptive study. A questionnaire was used to collect research data. The research questionnaire was completed by 46 out of 52 students in the third semester and beyond of the master's degree in auditing at public universities in the country, as well as by 28 out of 51 academic staff members of these universities. The resulting data were analyzed using SPSS software, and a one-sample t-test was performed.ResultsThe findings of this research indicate that, from the professors' perspective, the desirability of all the elements of the master's curriculum in auditing—including objectives, learning activities, content, teaching strategies, time, place, evaluation, grouping, and educational materials and resources is at an average level. In contrast, from the students' perspective, the desirability of the elements related to learning activities, teaching strategies, and educational materials and resources is rated as inappropriate, while the desirability of the elements concerning goals, content, learning activities, time, place, grouping, and evaluation is at an average level. ConclusionThe results of the survey indicate that the quality of the Master of Auditing curriculum is unfavorable in all nine elements of internal curriculum quality and needs to be revised. Regarding the "goal" element, although the goal is clearly stated in this curriculum, there has not been enough attention paid to the simultaneous development of knowledge (theoretical topics) alongside skills (such as communication, problem-solving, decision-making, writing, teamwork, etc.) and attitudes (such as creativity, innovation, social responsibility, and adherence to ethical principles). The focus of this program has primarily been on increasing the "knowledge" of the students. On the other hand, while "the content of this curriculum" is appropriate to the discipline's structure, it does not include the latest scientific theories and findings. Additionally, in terms of the time element, the hours (number of units) allocated to the courses do not align with the content of these courses. Some courses, such as management accounting and accounting theories, are allocated more hours than necessary and would be better replaced with new courses that address the changing needs of society and the labor market, such as big data analysis, advanced statistics, advanced specialized auditing software, computer and artificial intelligence-based auditing, econometrics, audit research, and internships. Furthermore, this program is not designed in a way that requires professors to use new and active teaching methods. Although the textbooks and resources mentioned in this curriculum are easily accessible to students, they are not up to date. The quality of learning in this curriculum is also lacking, which is partially rooted in inadequate attention to teaching strategies. Additionally, the grouping of learners is neglected in this curriculum; however, with the development of social networks and new technologies, it is possible to utilize available resources to enhance the quality of this element as well as educational equity. Finally, considering the unfavorable quality of the student evaluation methods in this curriculum, it seems that continuous assessments and other modern evaluation methods should be considered by the reviewing authorities of this curriculum.